Kekerasan Gender pada masa Pacaran - Rinja, Rinja; Adijaya, Sarlan; Laxmi, Laxmi (JURNAL KABANTI: Kerabat Antropologi, 2024)
This study aims to determine and describe the reasons for dating violence. The informants in this study amounted to 8 people, with the criteria of informants chosen, namely people who have been dating, are dating and have experienced violence during the dating period. Data collection in this study was casual observation and in-depth interviews. The results showed that the occurrence of violence was caused by unequal relations between men and women, dependence on boyfriends, excessive male dominance as boyfriends